Rekonseptualisasi Insan Kamil Abd Al-Karim Al-Jili Oleh Murtadha Muthahhari - Kurniawan; Encung (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The concept of Insan kamil (the perfect man) is one of the important themes in the Sufism. One of the evidence that could be peculiary noted is the witten books of Sufism about the human and perfection. And among the Sufis who studied intensively the concept of Insan Kamil is Murtadha Muthahhari. according to Murtadha Muthahhari, Insan Kamil is man who lives according to the contents of al-Qur’an and hadist. This reseaech focuses on the concept of Insan Kamil Murtadha Muthahhari. and basically the concept of Insan Kamil Murtadha Muthahhari has different characteristics with the consept of Insan Kamil al-Jili. Therefore, this research looks for the a side comparison between the concept of Insan Kamil al-Jili and Murtadha Muthahhari. the research method used is a method of hermeneutic interpretation and there are two kinds of data used; namely primary and secondary. In this case, the researcher uses literature sources and it is hoped this research can become a reference for figures who want to study the concept of Insan Kamil.